EPIDEMIOLOGY OF ZOONOTIC Cryptosporidium spp. ISOLATES IN NJORO SUB_COUNTY NAKURU COUNTY, KENYA - Walter, Essendi Miding’a; Elick, Otachi; Charles, Muleke; Manfred, Miheso (African Journal of Infectious Diseases (AJID), 2021)
ABSTRACT Cryptosporidium spp. are coccidian, oocysts-forming apicomplexan protozoans, which complete their life cycle both in humans and animals. In this study, Cryptosporidium spp. circulating in human and domestic animals along Njoro sub county was evaluated using microscopy with an aim of determining the level of Cryptosporidium spp. infections in domestic animals and humans. A total of 1476 animal and 378 human fecal samples were collected from homesteads and public health facilities, respectively within the Sub County These samples were processed, purified and oocysts isolated from microscopically positive stool samples. Data was subjected to an Analysis of Variance (ANOVA), t-test and Chi-square tests using R-Studio software to compare the differences in prevalence of Cryptosporidium spp. oocysts between feacal samples of human and animals with regard to parasitemia, season, age, sex and source of water at a 5% level of significance.Results of the study showed Cryptosporidium spp. was more prevalent in domestic animals than in humans. Prevalence of Cryptosporidium spp. in humans is significantly higher in females than in males. Cryptosporidium spp. infection is higher in the older individuals and children and lowest in adolescents and adults. The prevalence of Cryptosporidium spp. was relatively higher in wet and rainy months peaking in July than in dry seasons where prevalence was lowest in December, January and February. The study has concluded that cryptosporidium spp. is prevalent in Njoro Sub County and has highlighted domestic animals as an important reservoir for Cryptosporidium spp. and potential source of zoonosis of this infection in humans.